Changes in Postures of Male Drivers Caused by Long-Time Driving - Marko Cvetkovic (2020)
Professional drivers spend the majority of the working time steering a vehicle in a prolonged static posture. Therefore, pain in a particular region of the can appear and lead to musculoskeletal disorders. This study investigates the range of adopted driving angles after long-time driving. Driving postures were analyzed in a laboratory using software to establish three-dimensional angles performed by the driver. Parametric (Paired Sample) and nonparametric (Wilcoxon) tests were implemented to determine if there is any statistically significant difference among joint angles during initial recording (from zero to the 5th min), 40th, 80th, and 120th min. Upper libs generated the most substantial change in adopted angles taking into account the 5th and 120th min. Comparing postures with another study it could be seen that the range of motion is more extensive in this study. The reason could be the participants' stature or lack of adjustment possibilities due to the interior dimensions of the driving simulator.